Structural basis for C. elegans pairing center DNA binding specificity by the ZIM/HIM-8 family proteins - Meili Li; Chengming Zhu; Zheng Xu; Mingjing Xu; Yan Kuang; Xinhao Hou; Xinya Huang; Mengqi Lv; Yongrui Liu; Yong Zhang; Ziyan Xu; Xu Han; et al. (Nature Communications)
Abstract Pairing center (PC) on each chromosome of Caenorhabditis elegans is crucial for homolog pairing and initiating synapsis. Within each PC, clusters of 11/12 bp DNA motif recruit one of four paralogous meiosis-specific proteins: ZIM-1, ZIM-2, ZIM-3, or HIM-8. However, the mechanistic basis underlying the specificity of ZIM/HIM-8-PC DNA interaction remains elusive. Here, we describe crystal structures of HIM-8, ZIM-1 and ZIM-2 DNA binding domains (ZF1, ZF2 and CTD) in complex with their cognate PC DNA motifs, respectively. These structures demonstrated the ZF1-2-CTD folds as an integrated structural unit crucial for its DNA binding specificity. Base-specific DNA-contacting residues are exclusively distributed on ZF1-2 and highly conserved. Furthermore, the CTD potentially contributes to the conformational diversity of ZF1-2, imparting binding specificity to distinct PC DNA motifs. These findings shed light on the mechanism governing PC DNA motif recognition by ZIM/HIM-8 proteins, suggesting a co-evolution relationship between PC DNA motifs and ZF1-2-CTD in shaping the specific recognition.